PLAN DE SUCESIÓN BASADO EN LA GESTIÓN POR COMPETENCIAS PARA LA CONTINUIDAD DE LA EMPRESA FAMILIAR CASO: TECNILLANTAS CAMPOS EIRL - Campos Palpa y Cols., Ruth Silvia (2019)
Family businesses dominate the world, because they have a stake in the market comprising 66% to 80%, however, only the best, most competitive, they will succeed and reach the goals, objectives they were created, which will contribute to the management of human resources to adapt to new economic, strategic and organizational. Therefore, we must take into account that the life of family businesses there is nothing immutable and perpetual, nothing is perfect or permanent in time, as modern organizations have become more complex and difficult to handle, forming the lack of information one of the problems frequently encountered when managers make decisions, is therefore the creation of a succession plan that can help to have a plan that serves as a contingency for any unforeseen situation and there is knowledge on the subject, and a skilled and trained to assume leadership when the withdrawal occurred, is there someone able to cope with new circumstances that exist in the future and thereby help identify situations, anticipate problems and facilitate decision-making. Taking into account the quantitative and qualitative importance they have in the economy and the lack of information on this research, it was considered attractive way to address this issue to contribute to the generation of knowledge.